Strength and conditioning and concurrent training practices in elite rugby union - Jones, T. W.; Smith, A.; Macnaughton, L. S.; French, D. N. (The Journal of Strength and Conditioning Research, 2016)
There is limited published research on strength and conditioning (S&C) practices in elite rugby union (RU). Information regarding testing batteries and programme design would provide valuable information to both applied practitioners and researchers investigating the influence of training interventions or preperformance strategies. The aim of this study was to detail the current practices of S&C coaches and sport scientists working in RU. A questionnaire was developed that comprised 7 sections: personal details, physical testing, strength and power development, concurrent training, flexibility development, unique aspects of the programme, and any further relevant information regarding prescribed training programmes. Forty-three (41 men, 2 women; age: 33.1 ± 5.3 years) of 52 (83%) coaches responded to the questionnaire. The majority of practitioners worked with international level and/or professional RU athletes. All respondents believed strength training benefits RU performance and reported that their athletes regularly performed strength training. The clean and back squat were rated the most important prescribed exercises. Forty-one (95%) respondents reported prescribing plyometric exercises and 38 (88%) indicated that periodization strategies were used. Forty-two (98%) practitioners reported conducting physical testing, with body composition being the most commonly tested phenotype. Thirty-three (77%) practitioners indicated that the potential muted strength development associated with concurrent training was considered when programming and 27 (63%) believed that strength before aerobic training was more favorable for strength development than vice versa. This research represents the only published survey to date of S&C practices in northern and southern hemisphere RU.